Exploration and practice of project-based blended teaching mode based on OBE-CDIO concepts-example of “Project Planning and Control” - Yuming Huang; Ningze Gao; Yang Zhang; Fei Cao (SHS Web of Conferences)
At present, there is a discrepancy between the overall goal of cultivating applied talents in the context of new engineering disciplines and the social demand, which leads to the problems of unimpressive student learning outcomes and low employment rate caused by the single traditional teaching mode. Based on the the educational philosophy of OBE (Outcome based education) and CDIO (Conceive--Design-Implement-Operate), this paper toke the course of “Project Planning and Control” in Henan University of Economics and Law as an example, and adopt the blended course mode of combining project task-driven and round table seminar to carry out the teaching reform of the course, which has the The design of four modular teaching contents, the construction of teaching method(70% of concentrated lectures and 30% of immersion seminars) and evaluation system were finnaly conpleted. so that students could improve their professionalism and practical application ability in real work tasks and professional scenarios, and complete the initial exploration of the comprehensive education path of “policy, position, course, competition and certificate”.